Screening for tuberculosis infection among newly arrived asylum seekers: Comparison of QuantiFERON®TB Gold with tuberculin skin test - Harstad Ingunn; Jeppesen Anette; Mannsåker Turid; Korsvold Gro; Oftung Fredrik; Winje Brita; Heier Berit; Heldal Einar (BMC Infectious Diseases, 2008)
Abstract Background QuantiFERON®TB Gold (QFT) is a promising blood test for tuberculosis infection but with few data so far from immigrant screening. The aim of this study was to compare results of QFT and tuberculin skin test (TST) among newly arrived asylum seekers in Norway and to assess the role of QFT in routine diagnostic screening for latent tuberculosis infection. Methods The 1000 asylum seekers (age ≥ 18 years) enrolled in the study were voluntarily recruited from 2813 consecutive asylum seekers arriving at the national reception centre from September 2005 to June 2006. Participation included a QFT test and a questionnaire in addition to the mandatory TST and chest X-ray. Results Among 912 asylum seekers with valid test results, 29% (264) had a positive QFT test whereas 50% (460) tested positive with TST (indurations ≥ 6 mm), indicating a high proportion of latent infection within this group. Among the TST positive participants 50% were QFT negative, whereas 7% of the TST negative participants were QFT positive. There was a significant association between increase in size of TST result and the likelihood of being QFT positive. Agreement between the tests was 71–79% depending on the chosen TST cut-off and it was higher for non-vaccinated individuals. Conclusion By using QFT in routine screening, further follow-up could be avoided in 43% of the asylum seekers who would have been referred if based only on a positive TST (≥ 6 mm). The proportion of individuals referred will be the same whether QFT replaces TST or is used as a supplement to confirm a positive TST, but the number tested will vary greatly. All three screening approaches would identify the same proportion (88–89%) of asylum seekers with a positive QFT and/or a TST ≥ 15 mm, but different groups will be missed.